Patient Blood Management Stewardship Campaign Nepal - Amatya, Ashish Govinda (Nepalese Heart Journal, 2022)
Although the World Health Organization has endorsed Patient blood management (PBM) in 2010 many hospitals still seek guidance with the implementation of PBM in clinical routine. This article presents how a Himalayan country; Nepal collaborate to form a task force to develop recommendation implementing PBM in clinical practice for improved outcomes.